Designing and tuning robust feedforward controllers - Adam, Eduardo Jose (2004)
A model-based design and tuning procedure for feedforward controllers, which accounts for model uncertainties of SISO systems. Proper relationships for the analysis of feedforward-feedback control systems shows that tuning the feedforward controller is not completely independent form the feedback loop spectral characteristic. Similarly, fine tune of the associated feedback controller requires to be based on the residual disturbance remaining after the feedforward control action. Consequently, the simultaneous tuning is proposed for efficiently solving disturbance-rejection problems. Two application example show that the robust combined tuning gives satisfactory results for different dynamic and different tuning requirements.